The management of climate displacement - Leckie, S (Refugee Studies Centre, University of Oxford, 2012)
Many of those who have fought against displacement now find themselves being advocates for resettlement and relocation. Knowing that displacements will occur as a result of climate change, the humanitarian community will need to work pre-emptively with communities identified as likely to be threatened on the landbased solutions that may be available to them.